In Which Magnetotail Hemisphere is a Satellite? Problems Using in Situ Magnetic Field Data. Issue 2 (19th February 2021) - De Spiegeleer, A.; Hamrin, M.; Gunell, H.; Pitkänen, T.; Chong, S.
Abstract: In Earth's magnetotail plasma sheet, the sunward‐tailward B x component of the magnetic field is often used to separate the region above and below the cross‐tail current sheet. Using a three‐dimensional magneto‐hydrodynamic simulation, we show that high‐speed flows do not only affect the north‐south magnetic field component (causing dipolarization fronts), but also the sunward‐tailward component via the formation of a magnetic dent. This dent is such that, in the Northern Hemisphere, the magnetic field is tailward while in the Southern Hemisphere, it is earthward. This is opposite to the expected signatures where B x  > 0 ( B x  < 0) above (below) the neutral sheet. Therefore, the direction of the magnetic field cannot always be used to identify in which hemisphere an in situ spacecraft is located. In addition, the cross‐tail currents associated with the dent is different from the currents in a tail without a dent. From the simulation, we suggest that the observation of a dawnward current and a tailward magnetic tension force, possibly together with an increase in the plasma beta, may indicate the presence of a magnetic dent. To exemplify, we also present data of a high‐speed flow observed by the Cluster mission, and we show that the changing sign of B x is likely due to such a dent, and not to the spacecraft moving across the neutral sheet. Plain Language Summary: In the middle of the plasma sheet in the Earth's magnetotail exists an electrical current sheet that separates the magnetic field pointing away from (toward) Earth in the Southern (Northern) Hemisphere. This property of the magnetic field is usually used to identify the region of observation. However, by analyzing results from a three‐dimensional simulation and in situ observations, we show that this property of the magnetic field may not always hold. Indeed, in the presence of a fast earthward flowing plasma confined near the current sheet region, the magnetic field may instead be observed to point toward (away from) Earth in the Southern (Northern) Hemisphere, that is, opposite to the usual configuration. This is because the fast earthward flow deforms the magnetic field lines in such a way that the field lines wrap around the forefront of the fast earthward flow. This wrapping of the magnetic field lines results in a magnetic field orientation opposite to what is expected, namely, it is earthward in the Southern Hemisphere and tailward in the Northern Hemisphere. Key Points: Simulation and Cluster data show dents in the magnetic field lines ahead of high‐speed flows Within a dent, Geocentric Solar Magnetospheric B x  > 0 ( B x  < 0) is observed in the Southern (Northern) Hemisphere Thus, using the sign of the measured B x to identify where a satellite is can lead to errors